Fin Tech – A game changer, risks and return - Solanki , Akash (Gyan Management Journal, 2024)
Fin Tech revolution can be traced to the global financial crisis. In theIndian context, the Fin Tech revolution has been primarily in the fieldof payment systems and there has been a quantum increase in the lastdecade. Regulators have taken a number of regulatory initiatives forthe development of Fin Tech landscape. The digital advancement is alsofraught with risks pertaining to mis-selling, data privacy and onlinefraud. Therefore, in order to harness the potential of digital innovations,it is important there is need for spreading awareness among regardingrisks associated with online/cyber transactions, there is also need forbolstering up the digital infrastructure and also cost effective technologyto reach the under privileged sections of the society.
Keywords: Fin Tech revolution can be traced to the global financial crisis